2013
DOI: 10.3389/fmicb.2013.00210
|View full text |Cite
|
Sign up to set email alerts
|

A key time point for cell growth and magnetosome synthesis of Magnetospirillum gryphiswaldense based on real-time analysis of physiological factors

Abstract: Pure culture of magnetotactic bacteria with high magnetosome yield has been achieved for only a few strains. The major obstacles involve the nutritional requirements and culture conditions of the cells. To increase cell density and magnetosome production, it is necessary to elucidate the physiological characteristics of a particular strain during cell growth and develop an appropriate artificial control strategy. Large-scale culture of Magnetospirillum gryphiswaldense strain MSR-1 was successfully performed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…Previous studies have shown that magnetosome development requires low oxygen concentration (Sch€ uler et al, 1998;Yang et al, 2013). In submerged culture of MSR-1, relative dissolved oxygen concentration (dO 2 ) < 1% was required for magnetosome formation (Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that magnetosome development requires low oxygen concentration (Sch€ uler et al, 1998;Yang et al, 2013). In submerged culture of MSR-1, relative dissolved oxygen concentration (dO 2 ) < 1% was required for magnetosome formation (Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Fermentation was carried out at 29.5 • C under agitation at 200 rpm during 2 days at pH maintained at 6.9 by adding an acidic fed-batch medium containing FeCl 3 .6H 2 O as the iron source. Growth of MSR-1 bacteria was stimulated by bubbling oxygen in the growth medium at a percentage of dO 2 kept below 1 % to enable magnetosome synthesis (Sun et al, 2008;Zhang et al, 2011;Yang et al, 2013;Fernández-Castané et al, 2018). Temperature, agitation speed, pH, feeding pump flow and oxygen concentration were monitored and adjusted using a DASGIP controller and a DASware software from Applikon Eppendorf.…”
Section: Culture Of Mtb In 15 L Bioreactormentioning
confidence: 99%
“…Despite numerous efforts to improve the yields of magnetosomes [4,12,13], their large-scale biomanufacture remains significant barrier to future widespread industrial application. Fundamental to this are: (i) appropriate means for analysing MTB growth and physiology [14,15]; (ii) investigating the biomineralization of magnetic iron-containing minerals, which is still not fully understood [16 -18]; (iii) the ability to both produce batches of nanoparticles that are consistent in structure, chain length and functionality -this is key to unlocking the potential of magnetosomes as therapeutic agents; and (iv) to be able to rapidly analyse these characteristics.…”
Section: Introductionmentioning
confidence: 99%